Identification of Hazards on Road Access in The Area of Universitas Negeri Semarang: Study to Determine Safety Transportation in The Campus Area - Rega Ahlunijar; Ayu Fadilah Wahid; M. Aulia Farhan Akmal; Caroline Kirana Christi Rengganis; Suci Karuniawati; Howen Kholim (Journal of Safety Education, 2023)
Occupational safety and health are all activities to guarantee and protect the safety and health of workers through efforts to prevent work accidents and work-related diseases. Occupational safety is inseparable from the factors that can lead to work accidents. One of the factors causing work accidents is danger. Therefore, hazard identification needs to be carried out within the scope of a work area. This paper discusses hazards on road access in the area of the Faculty of Sports Science (FIK). The point taken is regarding vehicle lanes and pedestrian paths in the FIK area because there are still several points that are still classified as hazard-prone areas. Road users in the area in their daily activities have the potential to be exposed to hazards in every aspect of the road access in the area. There is an equally wide range of hazards in the workplace namely, physical, biological, psychosocial, chemical and ergonomic hazards. After that, accidents, illness, and even death are likely to occur in the Area.